Human Rights in Contemporary Society Challenges From an International Perspective - Mali, Jana; Mali, Jana (IntechOpen, 2024)
We are often confronted with unknown events that plunge us into ignorance, unpredictability, and various hardships. In such situations, it is essential how fundamental human values and rights such as dignity, freedom, equality, and solidarity are protected. Ensuring human rights in contemporary society is a complex area described in this book from the perspective of conceptualising and defining human rights, institutional responses, and practices to protect human rights, ensuring social justice and equality in contemporary society. The book is a compilation of interdisciplinary and international experiences in researching human rights, responding to human rights violations, and ensuring the enforcement of rights at the level of the daily lives of individuals, communities, and society as a whole.
English
Keywords: Sociology